Removal of Antibiotics from Real Hospital Wastewater by Cold Plasma Technique - Phuong Thi Thanh Nguyen; Hieu Trung Nguyen; Uyen Nhat Phuoc Tran; Ha Manh Bui (Journal of Chemistry)
Hospital wastewater contains a complex mixture of bioactive substances and microorganisms that are deleterious to humans and aquatic animals. In this study, four antibiotics, namely, ofloxacin, ciprofloxacin, cefuroxime, and amoxicillin, respectively, from the wastewater of seven hospitals in Ho Chi Minh City, Vietnam, were monitored. The results revealed that the wastewater from these hospitals is contaminated with at least one of the antibiotics. In addition, the degradation capacity of the antibiotics by the wastewater treatment plant at one of the hospitals by the cold plasma technique was investigated. Furthermore, effects of the variation in pH, interelectrode distance, applied voltage, and reaction time on the removal efficiency were investigated in terms of the reduction in antibiotics concentration, COD, and ammonia. Ciprofloxacin, cefuroxime, COD, and ammonia were almost eliminated, while ofloxacin and amoxicillin were reduced by more than 72% under optimum conditions (initial pH of 10, reaction time of 15 min, applied voltage of 30 kV, and interelectrode distance of 10 mm). All of these factors affected the removal efficiency. The removal efficiency was most robust in the first 5 min, and it increased with the increase in the reaction time. However, the removal efficiency tended to saturate over time, while it decreased with the increase in the reaction time. With an applied voltage of 30 kV onwards, the removal efficiency was not significantly different. Most of the pollutants were predominately eliminated under slightly alkaline conditions (pH of ∼10). In addition, primary oxidants in the aqueous phase, such as O3, H2O2, and ⋅OH, were generated. Besides, the obtained results also revealed that the decomposition of ciprofloxacin and cefuroxime follows the first-order reaction kinetics; meanwhile, the third-order reaction kinetics was most likely for the decomposition of ofloxacin and amoxicillin.